Simplify the following functions:

$1)\ \ \frac{x^2+x}{x^2-1}=\frac{x\left(x+1\right)}{\left(x+1\right)\left(x-1\right)}=\ \frac{x}{\left(x-1\right)}$

$\\$

$2)\ \ \frac{x^2-16}{{\left(x+4\right)}^2}=\frac{\left(x-4\right)\left(x+4\right)}{\left(x+4\right)\left(x+4\right)}=\frac{x-4}{x+4}$

$\\$

$3)\ \ \frac{a^2-b^2}{a^2b-{ab}^2}=\ \frac{\left(a-b\right)(a+b)}{ab(a-b)}=\frac{(a+b)}{ab}$

$\\$

$4)\ \ \frac{a^2+ab}{{2a}^3b-{2ab}^3}\ =\frac{a\left(a+b\right)}{2ab\left(a^2-b^2\right)}=\frac{a\left(a+b\right)}{2ab\left(a-b\right)\left(a+b\right)}=\frac{1}{2\ b\ \left(a-b\right)}$

$\\$

$5)\ \ \frac{x^2-9}{x^2+x-6}=\frac{\left(x-3\right)\left(x+3\right)}{\left(x+3\right)\left(x-2\right)}=\frac{\left(x-3\right)}{\left(x-2\right)}$

$\\$

$6)\ \ \frac{x^2-2x}{x^2+3x-10}=\frac{x\left(x-2\right)}{\left(x+5\right)\left(x-2\right)}=\frac{x}{\left(x+5\right)}$

$\\$

$7)\ \ \frac{x+3}{x^2-x-12}=\frac{x+3}{\left(x-4\right)\left(x+3\right)}=\frac{1}{x-4}$

$\\$

$8)\ \ \frac{x^2+2x-15}{x^2+4x-21}=\frac{\left(x+5\right)\left(x-3\right)}{\left(x+7\right)\left(x-3\right)}=\frac{x+5}{x+7}$

$\\$

$9)\ \ \frac{x^2-5x+4}{x^2-3x-4}=\frac{\left(x-1\right)\left(x-4\right)}{\left(x+1\right)\left(x-4\right)}=\frac{x-1}{x+1}$

$\\$

$10)\ \ \frac{x^3-{xy}^2}{x^3+{2x}^2y+{xy}^2}=\frac{x\left(x-y\right)\left(x+y\right)}{x^2\left(x+y\right)+2y\left(x+y\right)}=\frac{x\left(x-y\right)\left(x+y\right)}{x\left(x+y\right)\left(x+y\right)}=\frac{x-y}{x+y}$

$\\$

$11)\ \ \frac{{2x}^2+7x+3}{{3x}^2+10x+3}=\frac{{2x}^2+x+6x+3}{3x^2+9x+x+3}$

$=\frac{x\left(2x+1\right)+3\left(2x+1\right)}{3x\left(x+3\right)+\left(x+3\right)}=\frac{\left(2x+1\right)(x+3)}{\left(3x+1\right)(x+3)}=\frac{2x+1}{3x+1}$

$\\$

$12)\ \ \frac{{2x}^2+x-3}{{3x}^2+x-4}=\frac{2x^2-2x+3x-3}{3x^2+4x-3x-4}$

$=\frac{2x\left(x-1\right)+3\left(x-1\right)}{3x\left(x-1\right)+4\left(x-1\right)}=\frac{\left(2x+3\right)\left(x-1\right)}{\left(3x+4\right)\left(x-1\right)}=\frac{2x+3}{3x+4}$

$\\$

$13)\ \ \frac{x^2-16}{x^2-9}\times{}\frac{x+3}{x+4}=\frac{\left(x-4\right)\left(x+4\right)\left(x+3\right)}{\left(x-3\right)\left(x+3\right)\left(x+4\right)}=\frac{x-4}{x-3}$

$\\$

$14)\ \ \frac{a^2-{ab}^2}{a^2-{16b}^2}\times{}\frac{a+4b}{a-3b}=\frac{\left(a-3b\right)(a+3b(a+4b)}{\left(a-4b\right)\left(a+4b\right)\left(a-3b\right)}=\frac{a+3b}{a-4b}$

$\\$

$15)\ \ \frac{x^2+6x+5}{x^2+5x}\times{}\frac{x^3-x}{x^2-1}=\frac{\left(x+1\right)\left(x+5\right)x\left(x-1\right)\left(x+1\right)}{x\left(x+5\right)\left(x-1\right)\left(x+1\right)}=(x+1)$

$\\$

$16)\ \ \frac{x+y}{x^2-xy}\div{}\frac{x^2+xy}{x-y}=\frac{x+y}{x(x-y)}\times{}\frac{x-y}{x(x+y)}=\frac{1}{x^2}$

$\\$

$17)\ \ \frac{x^2-5x}{2x-3y}\div{}\frac{x^2-25}{{4x}^2-9y^2}=\frac{x\left(x-5\right)}{\left(2x-3y\right)}\times{}\frac{\left(2x-3y\right)\left(2x+3y\right)}{\left(x-5\right)\left(x+5\right)}=\frac{x(2x+3y)}{(x+5)}$

$\\$

$18)\ \ \frac{x^2+2-6}{x^2+2x-3}\div{}\frac{x^2+5x-14}{x^2+4x-5}=\frac{\left(x+3\right)\left(x-2\right)}{\left(x+3\right)\left(x-1\right)}\times{}\frac{\left(x+5\right)\left(x-1\right)}{\left(x+7\right)\left(x-2\right)}=\frac{x+5}{x+7}$

$\\$

$19)\ \ \frac{{3x}^2-x-2}{x^2+x-2}\div{}\frac{{3x}^2-7x-6}{x^2-x-6}$

$=\frac{{3x}^2-3x+2x-2}{x^2+2x-x-2}\times{}\frac{x^2-3x+2x-6}{3x^2-9x+2x-6}$

$=\frac{3x\left(x-1\right)+2\left(x-1\right)}{x\left(x+2\right)-1\left(x+2\right)}\times{}\frac{x\left(x+2\right)-3\left(x+2\right)}{3x\left(x-3\right)+2\left(x-3\right)}$

$=\frac{\left(3x+2\right)\left(x-1\right)}{\left(x-1\right)\left(x+2\right)}\times{}\frac{\left(x+2\right)\left(x-3\right)}{\left(x-3\right)\left(3x+2\right)}=1$

$\\$

$20)\ \ \frac{{2x}^2-3x-2}{x^2+7x+12}\times{}\frac{x^2+x-12}{x^2+3x-10}\div{}\frac{{2x}^2-5x-3}{x^2+8x+15}$

$=\frac{{2x}^2-4x+x-2}{\left(x+4\right)\left(x+3\right)}\times{}\frac{\left(x+4\right)\left(x-3\right)}{\left(x+5\right)\left(x-2\right)}\times{}\frac{\left(x+3\right)\left(x+5\right)}{{2x}^2-2x+3x-3}$

$=\frac{2x\left(x-2\right)+\left(x-2\right)}{\left(x+4\right)\left(x+3\right)}\times{}\frac{\left(x+4\right)\left(x-3\right)}{\left(x+5\right)\left(x-2\right)}\times{}\frac{\left(x+3\right)\left(x+5\right)}{\left(2x+1\right)\left(x-3\right)}=1$

$\\$

$21)\ \ \frac{2x+3}{3}-\frac{2x-4}{4}$

$=\frac{4\left(2x+3\right)-3\left(2x-4\right)}{12}$

$=\frac{8x+12-6x+12}{12}=\frac{2x+24}{12}=\frac{x+12}{6}$

$=\frac{3}{x-1}-\frac{3}{x+1}$

$=\frac{3\left(x+1\right)-3\left(x-1\right)}{\left(x-1\right)\left(x+1\right)}$

$=\frac{3x+3-3x+3}{\left(x-1\right)(x+1)}=\frac{6}{\left(x-1\right)(x+1)}$

$\\$

$22)\ \ \frac{3x-1}{4x}+\frac{3-5x}{12x}$

$=\frac{12x\left(3x-1\right)+4x\left(3-5x\right)}{48x^2}$

$=\frac{3}{x-1}-\frac{3}{x+1}$

$=\frac{3\left(x+1\right)-3\left(x-1\right)}{\left(x-1\right)\left(x+1\right)}$

$=\frac{3x+3-3x+3}{\left(x-1\right)(x+1)}=\frac{6}{\left(x-1\right)(x+1)}$

$\\$

$23)\ \ \frac{3x-1}{4x}+\frac{3-5x}{12x}$

$=\frac{12x\left(3x-1\right)+4x\left(3-5x\right)}{48x^2}$

$=\frac{36x^2-12x+12x-20x^2}{48x^2}=\frac{{16x}^2}{48x^2}=\frac{1}{3}$

$\\$

$24)\ \ \frac{x}{x-1}-\frac{x^2}{x^2-1}=\frac{x\left(x^2-1\right)-x^2\left(x-1\right)}{\left(x-1\right)\left(x-1\right)\left(x+1\right)}$

$=\frac{x^3-x-x^3++x^2}{\left(x-1\right)\left(x-1\right)\left(x+1\right)}=\frac{x\left(x-1\right)}{\left(x-1\right)\left(x-1\right)\left(x+1\right)}$

$=\frac{x}{\left(x-1\right)(x+1)}$

$\\$

$25)\ \ \frac{6}{a+b}-\frac{5}{a-b}+\frac{11b}{a^2-b^2}$

$=\frac{6\left(a-b\right)-5\left(a+b\right)+11b}{\left(a-b\right)\left(a+b\right)}$

$=\frac{6a-6b-5a-5b+11b}{\left(a-b\right)(a+b)}$

$=\frac{a}{\left(a-b\right)\left(a+b\right)}$

$\\$

$26)\ \ \frac{6}{x-2}+\frac{8}{2x-4}$

$=\frac{6\left(2x-4\right)+8\left(x-2\right)}{\left(x-2\right)\left(2x-4\right)}=\frac{12x-24+8x-16}{\left(x-2\right)\left(2x-4\right)}$

$=\frac{20x-40}{\left(x-2\right)\left(4-4\right)}=\frac{20\left(x-2\right)}{\left(x-2\right)\left(x-4\right)}=\frac{20}{x-4}$

$\\$

$27)\ \ \frac{1}{x^2-11x+30}+\frac{1}{x^2-9x+20}$

$=\frac{1}{\left(x-6\right)\left(x-5\right)}+\frac{1}{\left(x-5\right)\left(x-4\right)}$

$=\frac{\left(x-4\right)+\left(x-6\right)}{\left(x-6\right)\left(x-5\right)\left(x-4\right)}$

$=\frac{2(x-5)}{\left(x-6\right)\left(x-5\right)\left(x-4\right)}=\frac{2}{\left(x-6\right)(x-4)}$

$\\$

$28)\ \ \frac{1}{x^2-8x+15}+\frac{1}{x^2-4x+3}-\frac{2}{\left(x^2-6x+5\right)}$

$=\frac{1}{\left(x-3\right)\left(x-5\right)}+\frac{1}{\left(x-3\right)\left(x-1\right)}-\frac{2}{\left(x-3\right)\left(x-2\right)}$

$=\frac{\left(x-1\right)\left(x-2\right)+\left(x-2\right)\left(x-5\right)-2\left(x-1\right)\left(x-5\right)}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x-5\right)}$

$=\frac{x^2-3x+2+x^2-7x+10-2x^2+12x-10}{\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x-5\right)}$

$=\frac{2(x+1}{\left(x-1\right)\left(x-2\right)\left(x-3\right)(x-5)}$

$\\$

$29)\ \ \frac{x-3}{x^2-7x+12}+\frac{2\left(x-1\right)}{x^2-4x+3}-\frac{3\left(x-4\right)}{x^2-5x+4}$

$=\frac{x-3}{\left(x-3\right)\left(x-4\right)}+\frac{2\left(x-1\right)}{\left(x-3\right)\left(x-1\right)}-\frac{3\left(x-4\right)}{\left(x-4\right)\left(x-1\right)}$

$=\frac{1}{\left(x-4\right)}+\frac{2}{\left(x-3\right)}-\frac{3}{\left(x-1\right)}$

$=\frac{x^2-4x+3+2x^2-10x+8-{3x}^2+21x-36}{\left(x-1\right)\left(x-3\right)\left(x-4\right)}$

$=\frac{7x-25}{\left(x-1\right)\left(x-3\right)(x-4)}$

$\\$

$30)\ \ \frac{x^2-x-6}{x^2-9}+\frac{x^2+2x-24}{x^2-x-12}$

$=\frac{\left(x-6\right)(x+1)}{\left(x-3\right)(x+3)}+\frac{\left(x+6\right)(x-4)}{\left(x-4\right)(x+3)}$

$=\frac{\left(x-6\right)\left(x+1\right)}{\left(x-3\right)\left(x+3\right)}+\frac{\left(x+6\right)}{\left(x+3\right)}$

$=\frac{(x^2-5x-6)+(x^2+3x-18)}{\left(x-3\right)\left(x+3\right)}$

$=\frac{{2x}^2-2x-24}{\left(x-3\right)(x+3)}=\frac{2\left(x-4\right)(x+3)}{\left(x-3\right)(x+3)}=\frac{2(x-4)}{(x-3)}$

$\\$

$31)\ \ \left(\frac{2x}{4x+1}-\frac{x}{2x+3}\right)\div{}\ \frac{10x+5}{2x+3}$

$=\frac{4x^2+6x-{4x}^2-x}{\left(4x+1\right)\left(2x+3\right)}\times{}\frac{2x+3}{5\left(2x+1\right)}$

$=\frac{5x(2x+3)}{5\left(4x+1\right)\left(2x+3\right)(2x+1)}=\frac{x}{\left(4x+1\right)(2x+1)}$

$\\$

$32)\ \ \left(\frac{a^2+a-12}{a^2+6a+8}+\frac{a^2-6a+5}{a^2-3a-10}\right)\ of\ \frac{a^2+8+12}{a^2+4a-12}\$
$=\left(\frac{\left(a+4\right)\left(a+3\right)}{\left(a+4\right)\left(a+2\right)}+\frac{\left(a-5\right)\left(a-1\right)}{\left(a-5\right)\left(a+2\right)}\right)\times{}\frac{(a+2)(a+6)}{(a+6)(a-2)}$

$=\left(\frac{a-3}{a+2}+\frac{a-1}{a+2}\right)=\ \frac{2a-4}{a-2}=2$